The Tolerance Value in Habiburrahman El Shirazy’s Novel Ayat-Ayat Cinta 2 - Anis Kurnia Miftahul Husna; Andayani Andayani; Suyitno Suyitno (Karsa: Journal of Social and Islamic Culture, 2017)
The value of tolerance which inherent in the individual soul in this era of globalization began to collapse. Therefore, there are many cases of intolerance that increase every year. The novel of Habiburrahman El Shirazy "Ayat-Ayat Cinta 2" created with a high content of tolerant attitude which is able to inspire readers to imitate the commendable attitude of tolerance in coexistence with a pluralistic society like Indonesia. The purpose of this study was to explain and describe the forms of tolerance values contained in the story in the novel Ayat-Ayat Cinta 2 by Habiburrahman El Shirazy. The technique of collecting data was done by purposive sampling according to subject matter that studied. Data analysis technique in this research was done by interactive analysis model, namely: (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusion. The forms of tolerance that were  highlighted in the novel Ayat-Ayat Cinta 2  mostly came from Muslims society in Scotland, thus reflecting the teachings of Islam, although there were some who came from Scotland or even non-Muslims. The use of forms of tolerance values in the novel Ayat-Ayat Cinta 2 was poured in sentence form, real action, and debate. The reflection of visible values of tolerance did not distinguish between social status, geographic position, and level of human education. This research reveals the story behind a fascinating soul-building novel. Using descriptive-qualitative methods, this study found superior side of a tolerant value in Habiburrahman El Shirazy's novel Ayat-Ayat Cinta 2. The values of tolerance were respect and appreciate human diversity.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i2.1341